Green Synthesis and Characterization of Biocompatible Gold Nanoparticles Using Solanum indicum Fruits - Punuri Jayasekhar Babu; Pragya Sharma; Sibyala Saranya; Ranjan Tamuli; Utpal Bora (Nanomaterials and Nanotechnology)
This paper reports on the eco‐friendly synthesis of gold nanoparticles (AuNPs) using Solanum indicum fruit extract (SFE). We have evaluated various parameters for synthesis of AuNPs such as SFE (0.03%), HAuCl4 (0.5 mM) and reaction time (20 seconds). The synthesized AuNPs were characterized with different physical techniques such as transmission electron microscopy (TEM), Fourier transform infrared (FT‐IR) spectroscopy, X‐ray diffraction (XRD) and energy dispersive X‐ray spectroscopy (EDX). TEM experiments showed that AuNPs presented an anisotropic shape and size ranging from 5‐50nm. FT‐IR spectroscopy revealed that biomolecules containing an amine group (–NH2), a carbonyl group, –OH groups and other stabilizing functional groups were adsorbed on the surface of the synthesized AuNPs. EDX showed the presence of the elements on the surface of the AuNPs. The cytotoxicity of the synthesized AuNPs were tested on two different human cancer cell lines, HeLa and MCF‐7 and were found to be nontoxic, thus providing an opportunity to be used in biomedical applications.